PENGARUH DIGITAL MARKETING DAN POTONGAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE (Studi Kasus pada Mahasiswa FE Prodi Manajemen Universitas Islam “45” Bekasi - Septyo Nugraha Yudhistira; Riska Putri; Fistiawirzani Sakiinah (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
This study aims to examine and analyze the effect of digital marketing and price discounts on 100 respondents obtained on purchasing decisions at the shopee marketplace. questionnaire and data analysis techniques multiple linear regression. The results of this study indicate that partially digital marketing has a significant positive effect on purchasing decisions of Management study program students at the Faculty of Economics, Islamic University of Bekasi 45 on the Shopee shopping platform. Partially, price discounts have a significant positive effect on purchasing decisions of students of the Management study program, Faculty of Economics, Islamic University 45 Bekasi, on the Shopee shopping platform. Simultaneously digital marketing and price discounts have a significant positive effect on purchasing decisions of Management study program students at the Faculty of Economics, Islamic University 45 Bekasi on the Shopee shopping platform. Keywords : Digital Marketing, Discounts, Purchase Decision